The nest structure and aeration system of Cornitermes cumulans (Kollar, 1832) (Isoptera: Termitidae) - Sanchez, Guilhermo; Peres Filho, Otávio; Salvadori, José Roberto; Nakano, Octávio (Pesquisa Agropecuaria Brasileira, 2014)
This paper deals with the nest structure and aeration system of Cornitermes cumulans (Kollar, 1832) (Isoptera, Termitidae), an important insect pest species existing in areas requiring mechanization. The structure was studied by cutting longitudinal intersections of the nest. The aeration system was analyzed by using a motorized thermonebulizator and a powder insufflator. The results indicated that the powder injection process did not provide information as to the structures involved with aeration. However, the tog produced by the thermonebulizator showed to be efficient to demonstrate the importance of the cavity that surrounds the nest base, in the aeration.